International development : growth and change - Singer, H. W. (New York : McGraw-Hill, 1964)
This book is concerned with the problems of the underdeveloped countries. It is arranged in six major parts: "The Prospects for Development"; "Some Current Issues in Development Theory"; "Planning and Financing Development"; "Some Issues of Trade and Aid"; "Problems and Experience: Africa"; and "Problems and Experience.
Includes bibliographical footnotes and index.
lje 02/10/2018
Loans
Keywords: Economic development; Developing countries